2014
DOI: 10.1108/lr-07-2013-0088
|View full text |Cite
|
Sign up to set email alerts
|

Faculty members’ perceptions towards institutional repository at a medium-sized university

Abstract: Purpose – The study aimed to investigate the perceptions of faculty members at a medium-sized university towards self-archiving and participation in institutional repositories (IRs). Design/methodology/approach – The research participants were from a medium-sized university. An online survey was distributed and a total of 217 responses were received which yielded a 40 per cent overall response rate. Faculty perceptions of the IR were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
2
9
1
1
Order By: Relevance
“…As per the observation of Kim 14, younger professors, and professors who have good technical skills, tended to self-archive in a higher proportion than others. This finding is similar to the result of Ogus and Assefa 15 , who found that seniority in faculty rank and faculty members 'perception of the repository is inversely proportionate. The author noted that scholarly productivity played a significant role in faculty members' perception and willingness to contribute rather than prior knowledge and experience of IRs.…”
Section: Literature Reviewsupporting
confidence: 89%
“…As per the observation of Kim 14, younger professors, and professors who have good technical skills, tended to self-archive in a higher proportion than others. This finding is similar to the result of Ogus and Assefa 15 , who found that seniority in faculty rank and faculty members 'perception of the repository is inversely proportionate. The author noted that scholarly productivity played a significant role in faculty members' perception and willingness to contribute rather than prior knowledge and experience of IRs.…”
Section: Literature Reviewsupporting
confidence: 89%
“…However, these results are consistent with most of those reviewed in the literature, which show that maturity and academic status are associated with greater participation in open access (Eger et al, 2015;Kim, 2011;Lwoga & Questier, 2015). Only one of the articles studied, belonging to a university in Ghana, indicated that older researchers were less involved in the repository because they consider it to be of poorer quality (Oguz & Assefa, 2014). Researchers normally see a conflict between the institutional open access mandate and pressure to publish in journals with a high impact factor.…”
Section: Analysis By Agesupporting
confidence: 81%
“…One European study found that "authors from the social sciences, humanities, and arts were more likely to be unsure about the meaning of open access" (Creaser et al, 2010, p. 152). Another study at a medium-sized university in the United States found that those in the humanities had a negative perception of IRs, but that an awareness and prior experience with repositories were not factors that influenced their overall perception (Oguz & Assefa, 2014). Other researchers have explored concerns from faculty in many disciplines regarding IRs that can be a barrier to depositing their work.…”
Section: Literature Reviewmentioning
confidence: 99%